Implementasi Komonikasi dalam Pemanfaatan Aplikasi Samsat Digital Nasional (Singnal) sebagai Digitalisasi Pelayanan Publik di Samsat Padang - Mulyadi, Yandra; Arif, Ernita; ., Azwar (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2025)
The digitalization era has driven the transformation of public services through digital technology. In Padang City, the implementation of the SIGNAL application by the Samsat office aims to optimize motor vehicle administration services, yet its execution faces technical, socio-cultural, and institutional barriers, such as connectivity issues, resistance from senior generations toward digital technology, and limitations in human resources and budget. This study aims to analyze the implementation of communication in the utilization of the SIGNAL application at Samsat Padang as a form of digitalization in public services, The research employed a qualitative method with a constructivist paradigm and a case study approach. Data analysis was conducted using Everett M. Rogers’ Diffusion of Innovation Theory as the main framework, supported by Excellent Service Theory and the Technology Acceptance Model (TAM) to measure perceived ease of use and perceived usefulness of the application. The NVivo 12 software was used to identify dominant themes in the implementation of digital communication. The findings revealed five main points: transformation of communication patterns from conventional to integrated digital systems; improved public service effectiveness with reduced processing time; integration of communication systems and data security; responsive communication mechanisms based on citizen feedback; and optimization of communication channels enabling human resource reallocation. Efforts to overcome obstacles included user education, multi-channel communication, engagement of local influencers, and continuous evaluation. Data showed an increase in application adoption from 322 transactions in 2021 to 9,126 in 2024, indicating successful digital communication implementation, though wider outreach is still required.